Homology-Based Design for Selective GSK-3 Peptide Inhibitors: Patent Applications and Type 2 Diabetes Mellitus - Chaves Santos, Camila; Chaves, Rodrigo; Cristina Borges, Ana; Oliveira de Castro, Michelle; Miranda Costa-Junior, Helio (Current Signal Transduction Therapy, 2013)
Protein kinases function in key steps in several physiopathological events; therefore the development of specific inhibitors to these enzymes presents new opportunities for the treatment of various diseases. Glycogen synthase kinase 3 (GSK-3) is a constitutively active serine/threonine kinase, whose dysfunction has been linked to several cases of insulin-resistant type 2 diabetes mellitus, Alzheimer’s disease and mood disorders. These findings make GSK-3 an attractive target for therapeutics, and several research groups and pharmaceutical companies have made significant efforts to develop new inhibitors with selective activity to different GSK-3 pathways. One of the strategies applied in the development of new inhibitors is based on protein-protein interactions between substrates or docking proteins of specific proteins kinases, creating peptides modulators designed to specifically inhibit those enzymes. Here, we discuss the development, signaling and the patent applications of specific peptides designed to inhibit GSK-3, their patent status and their potential uses in the treatment of GSK-3 specific pathologies.
Keywords: rational peptide design